Quantum electrodynamics effects on NMR magnetic shielding constants of He-like and Be-like atomic systems - Giménez, Carlos Ariel (2016)
NMR shielding constants for He- and Be-like atomic systems of Ne, Ar, Kr, Xe, and Rn have been calculatedat the random-phase-approximation level of approach, including an estimation of QED corrections within the polarization propagator formalism. We show that QED effects enhance electron correlation when Z becomesheavier, which happens with relativistic effects, and also that QED effects become smaller when going from more to less ionized systems. We studied two- and four-electron systems. Then such studies could easily be generalized to other many-electron systems. Results of calculations with our relatively simple model, which includes QED and electron correlation effects on the same theoretical grounds, have a summarized error in the range from 10% (for Ne) up to 24% (for Rn), so that our accuracy is a little lower than for calculations on H-like systems.Our findings should stimulate the development and/or the application of more rigorous formalisms to get more accurate QED corrections to response properties in many-electron systems.